2010
DOI: 10.1016/j.abb.2010.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The kinetic mechanism of human uridine phosphorylase 1: Towards the development of enzyme inhibitors for cancer chemotherapy

Abstract: Uridine phosphorylase (UP) is a key enzyme in the pyrimidine salvage pathway, catalyzing the reversible phosphorolysis of uridine to uracil and ribose-1-phosphate (R1P). The human UP type 1 (hUP1) is a molecular target for the design of inhibitors intended to boost endogenous uridine levels to rescue normal tissues from the toxicity of fluoropyrimidine nucleoside chemotherapeutic agents, such as capecitabine and 5-fluorouracil. Here, we describe a method to obtain homogeneous recombinant hUP1, and present init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 36 publications
3
30
1
Order By: Relevance
“…A steady-state random mechanism is also compatible with isotope-trapping experiments and kinetic isotope effect measurements with arsenate as the nucleophile, which ruled out any ordered mechanism with the nucleophile binding first and a steady-state ordered mechanism with uridine binding first to the enzyme (11). These results differ from the steady-state ordered mechanisms reported for human type 1 (6) and rat (23) UPs in which P i is the first substrate to bind. Rapid-equilibrium random mechanisms have been proposed for UPs from E. coli (4) and Lactobacillus casei (24).…”
Section: Resultscontrasting
confidence: 99%
“…A steady-state random mechanism is also compatible with isotope-trapping experiments and kinetic isotope effect measurements with arsenate as the nucleophile, which ruled out any ordered mechanism with the nucleophile binding first and a steady-state ordered mechanism with uridine binding first to the enzyme (11). These results differ from the steady-state ordered mechanisms reported for human type 1 (6) and rat (23) UPs in which P i is the first substrate to bind. Rapid-equilibrium random mechanisms have been proposed for UPs from E. coli (4) and Lactobacillus casei (24).…”
Section: Resultscontrasting
confidence: 99%
“…32 The specificity of TcUP for uridine and 2′-deoxyuridine is comparable, evidenced by the similar values of the specificity constants ( k cat K M ). Thus, the ribosyl 2′-OH group is not essential for substrate binding or catalysis.…”
Section: Resultsmentioning
confidence: 90%
“…It is suggested that Pi binds to the free enzyme followed by uridine. Uracil then leaves the ternary complex, followed by dissociation of ribose-1-phosphate [19].…”
Section: Resultsmentioning
confidence: 99%